Additions to the checklist of Scoliidae, Sphecidae, Pompilidae and Vespidae of Peru, with notes on the endemic status of some species (Hymenoptera, Aculeata) - Santos, Eduardo Fernando dos [UNESP]; Grandinete, Yuri Campanholo [UNESP]; Noll, Fernanfo Barbosa [UNESP] (Pensoft Publ, 2015)
The first checklist of the Peruvian Hymenoptera listed 1169 species and subspecies of aculeate wasps, including 173 species of Pompilidae, seven of Scoliidae, 39 of Sphecidae and 403 of Vespidae. Herein are reported 32 species as new for Peru based mainly on the collection of the Natural History Museum, London. The loss of the endemic status of two species is also reported: Entypus peruvianus (Rohwer) (Pompilidae: Pepsinae) and Omicron ruficolle schunkei Giordani Soika (Vespidae: Eumeninae).
Keywords: Apoidea; Vespoidea; endemic species; social wasps; potter wasps; spider wasps; digger wasps